Disability in the Midst of YouTube Social Media Attraction in Religious Programs on the Hafiz Indonesia Channel - Ardianto, Aan (Institut Agama Islam Negeri Kerinci, 2023)
This research focuses on understanding the relationship between disability and media logic in religious programs, specifically in the Hafiz Indonesia program that aired during the month of Ramadan. It received significant appreciation, as evidenced by the number of subscribers on the Hafiz Indonesia YouTube channel, which reached 1.53 million. The data was collected through observation of YouTube social media and analyzed using Charles Sanders Peirce’s semiotic theory, which develops a triadic model known as the “triangle meaning semiotics,” as well as Brewis Alexander’s body image theory. The findings of this study reveal that there is still stereotyping of individuals with disabilities in the media, with the media often portraying them as models of resolution and restraint.